Implementasi Tata Kelola Sekolah Berbasis Karakter bagi Siswa Sekolah Menengah Kejuruan (SMK) Bhakti Luhur Malang - Goo, Maria Yulianti (SAPA - Jurnal Kateketik dan Pastoral, 2020)
English: The purpose of this article is to describe character-based school governance in vocational high schools using qualitative descriptive methods through literature review, observation and interviews. Through literature studies to see theories as a reference source. Observations and interviews, the authors made observations and interviews to obtain the required data related to the implementation of character-based school governance that was applied at Bhakti Luhur Malang Vocational School. The results obtained are that character-based school governance is a planned and structured joint movement process, thus the application of character-based management systems is actually the planting of beliefs or beliefs that form the basis for a person or group of people or organization to choose their actions or judge something meaningful or not meaningful to his life with his appraisal system based on rank or scale of values for his life. Thus to find out the school governance based on values that lead to character can be seen from the meaning of reality in the form of action, behavior, mindset, and attitude of a person or group of people in a school organization that flows from the vision, mission and goals of the school: to become a professional social worker for disabled, sick, neglected and elderly people. Indonesia: Artikel ini bertujuan mendeskripsikan tata kelola sekolah berbasis karakter di SMK Bhakti Luhur dengan menggunakan metode deskriptif kualitatif melalui kajian literatur, observasi dan wawancara. Melalui kajian literatur hendak melihat teori-teori sebagai sumber referensi. Observasi dan wawancara untuk mendapatkan data-data terkait dengan pelaksanaan tata kelola sekolah berbasis karakter yang diterapkan. Hasil yang diperoleh bahwa tata kelola sekolah berbasis karakter merupakan proses gerakan bersama yang terencana dan terstruktur untuk menanamkan nilai keyakinan atau kepercayaan yang menjadi dasar bagi seseorang atau sekelompok orang atau organisasi untuk memilih tindakannya atau menilai sesuatu yang bermakna atau tidak bermakna bagi kehidupannya dengan sistem penilaiannya berdasarkan peringkat atau skala nilai-nilai bagi hidupnya. Dengan demikian untuk mengetahui tata kelola sekolah bersumber pada nilai yang mengarah pada karakter dapat dilihat dari pemaknaan terhadap kenyataan-kenyataan berupa tindakan, tingkah laku, pola pikir, dan sikap seseorang atau kelompok dalam sebuah organisasi sekolah yang mengalir dari visi, misi dan tujuan sekolah: menjadi pelayan sosial yang profesional bagi para penyandang disabilitas, sakit, terlantar dan lanjut usia.